2019
DOI: 10.3390/su11082408
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Service Quality and Customer Loyalty: The Role of Customer Satisfaction and Switching Costs in the Pakistan Cellphone Industry

Abstract: Generally, the current scenario in the hyperactive corporate world, and specifically in the telecom sector, renders companies to compete concurrently on two fronts: Expansion of their customer base and the retention of their current customers. In order to explore and examine the latter concept, the current study hypothesizes the effects of sustainable service quality on customer loyalty with a mediating role of customer satisfaction conceptualized through the reciprocity theory. The study also considers the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 61 publications
7
36
0
2
Order By: Relevance
“…In the context of mobile phone services, there is evidence of switching cost having a moderating effect on the satisfaction-loyalty relationship where dissatisfied customers may not defect because of high switching cost (Lee et al , 2001). This moderating effect of switching cost in the mobile industry has been met with mixed findings as Hadi et al (2019) found that satisfied customer will remain loyal even if the switching cost is low. There is also evidence that tweens (8–12-year-old) are far more satisfied with mobile phones than adults yet brands are not able to turn these youngsters into loyal customers to recommend the product to friends (Martensen, 2007).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…In the context of mobile phone services, there is evidence of switching cost having a moderating effect on the satisfaction-loyalty relationship where dissatisfied customers may not defect because of high switching cost (Lee et al , 2001). This moderating effect of switching cost in the mobile industry has been met with mixed findings as Hadi et al (2019) found that satisfied customer will remain loyal even if the switching cost is low. There is also evidence that tweens (8–12-year-old) are far more satisfied with mobile phones than adults yet brands are not able to turn these youngsters into loyal customers to recommend the product to friends (Martensen, 2007).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…The effects quality of service has on customer satisfaction and loyalty have also yielded a broad field of research. Thus, in a study applied to the telecommunications sector, [28] showed that customer satisfaction plays a significant role, unlike the effect of switching cost. This explains why a satisfied customer will remain loyal even when the switching cost is low.…”
Section: Quality Of Information and Online Platformsmentioning
confidence: 99%
“…To enhance customers' awareness regarding sustainability, Ting et al [27] studied green customers of a Taiwanese hotel. Hadi et al [9] investigated the relationship between sustainable service quality and customer loyalty in the Pakistan cellphone industry. By designing a sustainable reverse logistics network, Cinar [3] developed a mixed integer linear programming (MILP) framework to determine a long-term strategy.…”
Section: Sustainability Organizations and Customersmentioning
confidence: 99%